The Influence of the Active Debate Method on Students' Critical Reasoning Ability - Witri Witri; Gimin Gimin; Indra Primahardani (Journal of Education Technology Information Social Sciences and Health, 2024)
The background to this research is because SMA Negeri 1 Pangean tends to learn conventionally, students are not given a learning experience, they are not trained in critical reasoning skills. So, when faced with a problem related to a learning topic, students experience difficulty in obtaining information and ideas, difficulty in analyzing and reasoning about information, and difficulty in concluding and conveying information clearly and systematically. Therefore, the lack of critical reasoning skills of students at SMA Negeri 1 Pangean deserves to be followed up and steps are needed to respond to and overcome the problems faced by students. One step that can be taken is to learn using the Active Debate method. The formulation of the problem in this research is whether there is an influence of the active debate method on the critical reasoning abilities of class XI students at SMA Negeri 1 Pangean. The population in this study were class XI students at SMA Negeri 1 Pangean with a total of 105 students. The sample in this study consisted of 70 students, who were divided into two classes, namely classes XI A and XI B. The data collection methods used in this research were observation, questionnaires. Data processing using statistical analysis using the t test formula, namely the Independent Sample T-test with a value of Sig.(2-tailed)=0.000 at a significance level of 5% or 0.0000.05, then Ha is accepted and Ho is rejected. So it can be concluded that the active debate method influences the critical reasoning abilities of class XI students at SMA Negeri 1 Pangean by obtaining an average score of 100% in the experimental class and an average of 90.32% in the control class.